DESIGN, SYNTHESIS OF BIOLOGICALLY ACTIVE HETEROCYCLES CONTAINING INDOL- THIAZOLYL- THIAZOLIDINONE DERIVATIVES - WALMIK, PRABHAKER; Naraboli, Basavaraj S; B, Swathi; Ghanti, Somashekhar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The present study envisage a novel series of thiazole, indole and thiazolidine derivatives, namely, N-((5-Substituted-2-phenyl-1 H-indol-3-yl)methylene)-4,5,6,7-tetrahydro-5,7,-dimethylbenzo [d]thiazole-2-amine (4a-c), 2-(5-substituted-2-phenyl-1H-indol-3-yl)-3-(4,5,6,7- trimethylbenzo[d]thiazol-2-yl)-thiazolidin-4-one (5a-c) and 5-benzylidine-2-(5-substituted-2phenyl-1H-indol-3yl)-3-(4,5,6,7-tetrahydro-5,5,7- trimethylbenzo[d]thiazol-2-yl) thiazolidin-4-one (6a-c). Methods: All the newly synthesized compounds were characterized by infrared, 1H, 13C nuclear magnetic resonance and mass spectral data and elemental analysis and evaluated for in vitro antimicrobial activity. Results: Novel compounds N-((5-Substituted-2-phenyl-1H-indol-3-yl)methylene)-4,5,6,7-tetrahydro-5,7,-dimethylbenzo [d]thiazole-2-amine (4a-c), 2-(5-substituted-2-phenyl-1H-indol-3-yl)-3-(4,5,6,7-trimethylbenzo[d]thiazol-2-yl)-thiazolidin-4-one (5a-c) and 5-benzylidine-2-(5-substituted- 2phenyl-1H-indol-3yl)-3-(4,5,6,7-tetrahydro-5,5,7-trimethyl benzo[d]thiazol-2-yl)thiazolidin-4-one (6a-c) have been made and characterized using spectral and analytical data. The results of antibacterial and antifungal activities showed that some of the synthesized compounds exhibited promising activities. Conclusion: All the newly synthesized compounds were carried out by the broth microdilution method (NCCLS. 2002) in a DMF concentration of 500, 250, 125, and 62.5 Î¼g/ml. Gentamycin and fluconazole are used as reference standards for antibacterial and antifungal activity, respectively. The final results revealed that compounds 4b, 5b, and 6b exhibited potent antimicrobial activity when compared to the standard drugs. Â